Brief report: Free-living physical activity levels and cognitive control in multi-problem young adults - van der Sluys, Maria Elise; Marhe, Reshmi; van der Laan, Peter H.; Popma, Arne; Scherder, Erik J. A. (Frontiers in Human Neuroscience, 2022)
Previous studies indicate a positive association between physical activity and cognitive control in sedentary but healthy adults, yet not much is known about physical activity levels in multi-problem young adults. We examined the level of self-reported free-living physical activity (i.e., MET minutes per week) in an ecological valid sample of young adults facing multiple problems, including unemployment, lack of education, frequent substance use, and history of delinquency. We compared cognitive control with an age- and sex-matched control sample. Additionally, the association between physical activity and cognitive control (i.e., response inhibition, error processing, interference effect) in the multi-problem group was examined. Physical activity and cognitive control were measured with the International Physical Activity Questionnaire-Long Form and three cognitive control experiments (i.e., Flanker, Go/NoGo, Stroop), respectively. With M = 4428 Metabolic Equivalents (METs), our multi-problem sample (n = 63) showed physical activity levels similar to the age- and sex-matched control sample from the general population (n = 62). The multi-problem young adults also showed impaired cognitive control indexed as decreased response inhibition and decreased Flanker correctness effect compared to their peers. We could not find an association between self-reported physical activity and cognitive control in the multi-problem sample. Due to the small sample size, results should be interpreted with caution. However, future dose-response studies could still use these results to further examine if within-individual increased physical activity may possibly lead to improved cognitive control in (already relatively active) multi-problem young adults.